1981
DOI: 10.1002/mpo.2950090214
|View full text |Cite
|
Sign up to set email alerts
|

Psychological late effects of leukemia in children and their prevention

Abstract: The psychological and intellectual sequelae of childhood leukemia and its treatment were examined in 48 children with acute leukemia in long remission. Verbal and performance IQ values were determined in addition to full scale IQ. Performance was worse than the verbal IQ in children who were less than six years old at the time of diagnosis. Cranial irradiation even in repeated doses of 2,400 rads had no effect on these children's intellects. Most of the patients, however, showed severe emotional problems when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Thus we have shown that the problem is related to treatment rather than psychosocial factors (Anderson et al, 1994). Dose of irradiation A number of previous studies have addressed the impact of high-or low-dose CRT, with little consensus with respect to findings (Trautman et al, 1988;Schuler et al, 1981;Appleton et al, 1990;Mulhern et al, 1992;Halberg et al, 1992;Hirsch et al, 1979). When our group 1 sample was subdivided into those who received a high dose (24 Gy) compared with a lower dose (18 Gy), it was found that the higher dose produced more adverse effects with regard to intellectual and educational abilities.…”
Section: Discussionmentioning
confidence: 76%
“…Thus we have shown that the problem is related to treatment rather than psychosocial factors (Anderson et al, 1994). Dose of irradiation A number of previous studies have addressed the impact of high-or low-dose CRT, with little consensus with respect to findings (Trautman et al, 1988;Schuler et al, 1981;Appleton et al, 1990;Mulhern et al, 1992;Halberg et al, 1992;Hirsch et al, 1979). When our group 1 sample was subdivided into those who received a high dose (24 Gy) compared with a lower dose (18 Gy), it was found that the higher dose produced more adverse effects with regard to intellectual and educational abilities.…”
Section: Discussionmentioning
confidence: 76%
“…Secondly, the VIQ-PIQ discrepancy which has been observed by a number of investigators (Eiser, 1978(Eiser, , 1980Meadows et al, 1981;Schuler et al, 1981) has been thought to reflect a deficit in perceptuo-visuo-spatial functioning. However, as has been pointed out by Kagan (1982), the majority of subtests which comprise the PIQ are timed tests.…”
Section: Discussionmentioning
confidence: 97%
“…An examination of the omitted studies indicates that their inclusion would not have changed the finding of a negative overall effect, although it may have affected its magnitude (with an unknown effect on moderator variables). Only one study (Schuler, Polcz, Revesz, Bakos & Gal, 1981) can be regarded as finding zero effect, on the basis that its subjects had a mean FIQ of 110. Seven of the others (numbers 22, 23, 25, 27, 28, 29 and 31 in Table 1) provide quite dear indications of FIQ decrements even if the authors report a "no effect" conclusion, and two (numbers 26 and 30) are indeterminate on FIQ although reporting more general adverse effects.…”
Section: Discussionmentioning
confidence: 99%